Olympic Problem on Functional Equations

Algebra Level 2

A function f f is defined on the set of integers, takes also integer values, and satisfies the functional equation f ( 2 a ) + 2 f ( b ) = f ( f ( a + b ) ) , f(2a)+2f(b)=f(f(a+b)) , for all integers a a and b . b. If f ( 0 ) = 2019 f(0)=2019 , find the largest possible value of f ( 2019 ) . f(2019).

Note: This problem is inspired on a problem of a contest.


The answer is 6057.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Aug 10, 2019

f ( 2019 ) = f ( f ( 0 ) ) = f ( f ( 0 + 0 ) ) = f ( 2 × 0 ) + 2 f ( 0 ) = 3 f ( 0 ) = 3 × 2019 = 6057 f(2019) = f(f(0)) = f(f(0+0)) = f(2\times0) + 2f(0) = 3f(0) = 3\times2019 =\boxed{6057}

Really nice, Mark! The original problem was to find all solutions, but when one changes the format of the problem to get just a value, there is always the risk that the problem becomes very easy like in this case. Brilliant for you!

Arturo Presa - 1 year, 10 months ago

Exact same solution

Matteo Bianchi - 1 year, 10 months ago

Same solution. Bit awkward how trivial the problem can become so simply even though it was based on an IMO problem. (2019 IMO Problem 1)

Razzi Masroor - 1 year, 8 months ago

But why would this be the largest ?

wing yan yau - 1 year ago

Log in to reply

It must be the largest possible value, since it is the only possible value.

Mark Hennings - 1 year ago

It is a trick. The solution is unique. So the largest is the only solution. If you ask for the value, then the reader already know that the solution will be unique from the beginning. It is a way of making the problems more challenging. Remember that in Brilliant the answer is always a number or the question is multiple choice. Some time is easy to get the answers, without doing the whole investigation of the problem

Arturo Presa - 1 year ago
Arturo Presa
Aug 9, 2019

Replacing in the given functional equation the a a by 0 and the b b by a + b , a+b, we obtain that f ( 0 ) + 2 f ( a + b ) = f ( f ( a + b ) ) . f(0)+2f(a+b)=f(f(a+b)). This equation and the one given in the problem imply that f ( 2 a ) + 2 f ( b ) = f ( 0 ) + 2 f ( a + b ) f(2a)+2f(b)=f(0)+2f(a+b) for any integer numbers a a and b . b. Now, making a = 1 , a=1, we get f ( 2 ) + 2 f ( b ) = f ( 0 ) + 2 f ( b + 1 ) f(2)+2f(b)=f(0)+2f(b+1) for all integers b. From this equation, we obtain that f ( b + 1 ) f ( b ) = f ( 2 ) f ( 0 ) 2 . f(b+1)-f(b)=\frac{f(2)-f(0)}{2}. Thus it can be proved by mathematical induction that f ( n ) = c n + r , f(n)=c n+r, where c c and r r are constant integers. Substituting this expression into the given functional equation, it is obtained that 2 c ( a + b ) + 3 r = c 2 ( a + b ) + c r + r . ( ) 2c(a+b)+3r=c^2(a+b)+cr+r.\:\:\:\:\:\:(*) Making a + b = 0 , a+b=0, moving all the terms to the left side and factoring, it follows the equation ( 2 c ) r = 0. ( ) (2-c)r=0.\:\:\:\:\:(**) Then there are two cases: r = 0 r=0 or r 0. r\neq0.

Case 1: When r = 0. r=0.

Substituting into equation (*), assuming that a + b 0 , a+b\neq 0, we get 2 c = c 2 . 2c=c^2. Then c = 0 c=0 or c = 2. c=2. Both values work, so we obtain that two of the possible solutions of the given equation are f ( n ) = 0 , f(n)=0, or f ( n ) = 2 n , f(n)=2n, for all integer values of n . n.

Case 2: When r 0. r\neq0.

The equation ( ) (**) implies that c = 2. c=2. Then it is easy to verify that making c = 2 c=2 and for any integer r r the equation ( ) (*) is true. Therefore, the remaining solutions of the given equation will be any function of the form f ( n ) = 2 n + r , f(n)=2n+r, where r r is any integer different from zero. We conclude that any solution of the given functional equation will be of the form f ( n ) = 0 f(n)=0 for any integer n , n, or the form f ( n ) = 2 n + r , f(n)=2n+r, where n n is any integer and r r is an arbitrary integer constant. Now, from the condition that f ( 0 ) = 2019 , f(0)=2019, it follows that the corresponding solution has the form f ( n ) = 2 n + 2019 , f(n)=2n+2019, for any integer n . n. Then f ( 2019 ) = 2 ( 2019 ) + 2019 = 6057. f(2019)=2(2019)+2019=\boxed{6057.}

Note: This problem was inspired by the first problem of the IMO2019.

It is a little simpler to consider the coefficient of a + b a+b at the same time as the constant coefficient, since then we have c ( c 2 ) = r ( c 2 ) = 0 c(c-2) = r(c-2) = 0 . Thus either c = 2 c=2 or r = c = 0 r=c=0 ...

Mark Hennings - 1 year, 10 months ago

I remembered the solution and the problem pretty well. So, I just had to find out the value of 2(2019)+2019=6057

Maalav Mehta - 1 year, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...